Size-controlled nanopores in lipid membranes with stabilizing electric fields - Fernández, María Laura (2012)
Molecular dynamics (MD) has been shown to be a useful tool for unveiling many aspects of pore formation in lipid membranes under the influence of an applied electric field. However, the study of the structure and transport properties of electropores by means of MD has been hampered by difficulties in the maintenance of a stable electropore in the typically small simulated membrane patches. We describe a new simulation scheme in which an initially larger porating field is systematically reduced after pore formation to lower stabilizing values to produce stable, size-controlled electropores, which can then be characterized at the molecular level. A new method allows the three-dimensional modeling of the irregular shape of the pores obtained as well as the quantification of its volume. The size of the pore is a function of the value of the stabilizing field. At lower fields the pore disappears and the membrane recovers its normal shape, although in some cases long-lived, fragmented pores containing unusual lipid orientations in the bilayer are observed.